Structural assessment and characterisation of the rock slope failure at Skredkallen, Vannøya. Structural analysis using field and desktop methods - Trønnes, Leif (UiT Norges arktiske universitet, 2019)
The University of Tromsø has carried out multiple studies by master students on unstable rock slopes (URS) in Troms County, Northern Norway. This thesis differs from other studies in Troms as Skredkallen is located in Pre-Cambrian rocks as part of West Troms Basement Complex (WTBC). The rocks of the WTBC have been subjected to multiple phases of deformation, and the main structural features from deformation at this field site is from a Paleoproterozoic thrust sheet, ‘Skipsfjord Nappe’, from Svecofennian deformation. Skredkallen is an actively deforming URS located on the steep eastern slope of Laukvikfjellet. Previous failure events have occurred in the URS, resulting in rock avalanche deposits of varying size below the slope. What is left is multiple detached terraces and a tall column of rock ‘Kaillen’, which is still actively deforming. The URS has been identified as moving downslope towards NE by means of satellite InSAR. The location of Skredkallen, as well as a rock slope failure on a mountain ridge further west, align with a thrust boundary. This suggests that there might be a regional pattern between the two instabilities and a possibility of a tectonic boundary forming the rupture surface of the URS. Geophysical data indicates a fault being present close to Skredkallen, and brittle fault structures have played an important role in the origin of the URS. The structural mapping showed four main joint sets; J1(034/82±16.9), J2(205/68±9.0), J3(309/68±10.5) and J4(117/83±15.5). J1 and J4 were the most dominant joint sets, both near-vertical and dipping towards ESE and SW respectively. The foliation (292/14±13.8) dipping towards NNE is oblique to the NE facing slope. The main failure mechanism is planar sliding along a NE-dipping failure surface, probably contributing to a biplanar compound slide made up by J3 and SF, which together have developed a step-path geometry effectively working as a listric sliding plane. The rock column Kaillen is toppling towards E from the intersection between J1 and J4. The ...